Carbon-coated ion-doped vanadium oxide material as well as preparation method and application thereof

By embedding metal ions in vanadium oxide and carbon coating, the problems of slow kinetics, low capacity and poor cycle stability caused by large ion radius of sodium ions in sodium ion batteries are solved, and the efficient cycle stability and electrochemical performance of the material are improved.

CN119764385AActive Publication Date: 2025-04-04ZHEJIANG UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411921173.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-04
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

Due to the large ion radius of sodium ions, sodium ion batteries have problems such as slow kinetics, low capacity and poor cycle stability.

Method used

The conductivity and cyclic stability of the material are improved by embedding metal ions (such as Fe3+, Ni2+, Cu2+) in the vanadium oxide and carbon coating.

Benefits of technology

The cycle stability and electrochemical performance of vanadium oxide materials are significantly improved, and the problems of low capacity and poor cycle stability of sodium ion batteries are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764385A_ABST
    Figure CN119764385A_ABST
Patent Text Reader

Abstract

The invention provides a carbon-coated ion-doped vanadium oxide material and a preparation method and application thereof, and the preparation method comprises the following steps: carrying out solvothermal reaction on a reaction solution containing doped metal ions, a vanadium oxide intermediate solution, an oxidant, a solvent and glucose, and calcining in a protective atmosphere to obtain a solid, preparing a carbon-coated ion-doped vanadium oxide material; the doped metal ions are selected from one or more of Fe < 3 + >, Ni < 2 + > and Cu < 2 + >. The metal ions are embedded into the vanadium oxide, so that the conductivity of the vanadium oxide material and the electrochemical stability of the vanadium oxide material in the cycle process are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material technology, and in particular to a carbon-coated ion-doped vanadium oxide material and a preparation method and application thereof. Background Art

[0002] With the consumption of non-renewable energy such as oil and fossil energy, global warming and energy depletion are becoming increasingly serious, and the development of clean and renewable energy is imminent. The vigorous promotion of clean energy such as wind energy, solar energy, and tidal energy has alleviated environmental problems to a certain extent, but these energy forms have disadvantages such as unstable power generation and great environmental impact. Therefore, rechargeable batteries have a wide range of application scenarios. They can not only be applied to transportation in life to reduce the consumption of fossil fuels, but also be applied to large-scale energy storage facilities to achieve efficient utilization of renewable resources. In the past few decades, lithium-ion batteries (LIBs) have played a vital role in human society with their advantages such as high energy density and long cycle life, but limited lithium mineral resources have hindered their continuous development; since sodium and lithium are in the same main group, have similar properties, and sodium reserves are very abundant, sodium-ion batteries have been favored by researchers as a substitute for lithium-ion batteries.

[0003] Although sodium-ion batteries have many advantages over lithium-ion batteries, they also face a series of problems. Compared with lithium-ion batteries, sodium ions have a larger ion radius, which limits their ion transport during the charge and discharge process of sodium-ion batteries, resulting in lower capacity than lithium-ion batteries. At the same time, sodium ions with a larger radius lead to multiple phase transitions during the charge and discharge process, resulting in changes in the material structure and reducing the cycle stability of the battery. Therefore, it is necessary to explore an excellent positive electrode material to solve the above problems.

[0004] Vanadium oxide materials have excellent performance in sodium ion batteries due to their rich and variable valence states and high theoretical capacity, but their cycle stability is poor in specific applications. Considering the above shortcomings, it is of great research value to improve the performance of vanadium oxide positive electrode materials by ion doping and carbon coating of ion-doped vanadium oxides. Summary of the invention

[0005] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a carbon-coated ion-doped vanadium oxide material and a preparation method and application thereof, so as to solve the problems of low capacity and poor cycle stability of existing sodium ion batteries.

[0006] In order to achieve the above-mentioned object and other related objects, the present invention provides a method for preparing a carbon-coated ion-doped vanadium oxide material, comprising subjecting a reaction solution containing doped metal ions, a vanadium oxide intermediate solution, an oxidant, a solvent and glucose to a solvothermal reaction, and calcining the obtained solid under a protective atmosphere to obtain a carbon-coated ion-doped vanadium oxide material; the doped metal ions are selected from Fe 3+ 、Ni 2+ and Cu 2+ One or more of .

[0007] The present invention completes the ion doping and carbon coating of vanadium oxide by one-step hydrothermal method and post-annealing. Compared with other multiple hydrothermal methods, the operation is simpler and the time consumption is shorter, which provides a useful reference for carbon-coated ion doped vanadium oxide. The method utilizes that the metal ions are doped into the vanadium oxide to widen the interlayer spacing, effectively enhancing the stability of the material, and at the same time, by carbon coating the material, the cyclic stability of the material is greatly improved.

[0008] Preferably, the chemical formula of the vanadium oxide intermediate in the vanadium oxide intermediate solution is VOC 2 O 4 .

[0009] Preferably, the preparation method of the vanadium oxide intermediate solution is: 2 O 5 The vanadium oxide intermediate solution is prepared by dispersing the vanadium oxide with oxalic acid in water and reacting at 60-80°C, preferably at 80°C, and the reaction time is preferably 1 h.

[0010] Preferably, the V 2 O 5 The mass ratio of the raw material to oxalic acid is (0.5~2):(1~5), and more preferably 1.2:2.49.

[0011] Preferably, the oxidant is selected from one or more of hydrogen peroxide, ammonium persulfate and potassium dichromate.

[0012] Preferably, the solvent is one or a combination of methanol and ethanol.

[0013] Preferably, the volume ratio of the vanadium oxide intermediate solution, the oxidant and the solvent is (10-50):(3-5):(10-30), more preferably 30:3:20.

[0014] More preferably, the order of adding the reaction solution is: firstly, the vanadium oxide intermediate solution is mixed with the oxidant and the solvent to obtain solution A, and then glucose and the doped metal ions are added to solution A.

[0015] Preferably, the doping metal ions are added in the form of soluble metal salts, and the mass ratio of the soluble metal salt to glucose is (0.05-0.2): (0.5-1).

[0016] More preferably, the feed ratio of the A solution, the soluble metal salt and glucose is (30-50) ml: (0.05-0.2) g: (0.5-1) g, and most preferably is 50 ml: 0.16 g: 0.9 g.

[0017] More preferably, the soluble metal salt is Fe(NO 3 ) 3 9H 2 O.Ni(NO 3 ) 2 6H 2 O and Cu(NO 3 ) 2 ·3H 2 Preferably, the solvent thermal reaction temperature is 160-200° C., and the reaction time is 24-48 h.

[0018] More preferably, the solvothermal reaction temperature is 170° C. and the reaction time is 48 h.

[0019] Preferably, the calcination temperature is 300-600° C., and the time is 1-3 h. The calcination temperature is more preferably 550° C., and the calcination time is more preferably 2 h.

[0020] Preferably, the calcination further includes solid-liquid separation, washing and vacuum drying steps.

[0021] More preferably, the obtained solid is repeatedly washed with deionized water and ethanol.

[0022] More preferably, the vacuum drying temperature is 60-80° C. and the time is 10-12.

[0023] The present invention also provides a carbon-coated ion-doped vanadium oxide material prepared by the above preparation method.

[0024] The present invention also provides a use of the carbon-coated ion-doped vanadium oxide material as a positive electrode active material in the preparation of a sodium ion battery.

[0025] As described above, the present invention has the following beneficial effects: (1) By embedding metal ions in vanadium oxide, the conductivity of vanadium oxide materials and the electrochemical stability during the cycle process are improved; (2) By carbon-coating the metal ion-doped vanadium oxide material, the collapse problem caused by the change in crystal spacing during the cycle is alleviated, greatly improving the cycle stability of the vanadium oxide material; (3) The raw materials of the present invention are convenient to source, have good stability, and the preparation method is simple to operate and has low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The carbon-coated ion-doped vanadium oxide (a) prepared in Example 1 and the VO prepared in Comparative Example 1 are shown. 2 (b) FeVO prepared in Comparative Example 2 2 (c) SEM image.

[0027] Figure 2 Shown are the TEM image (a) and the corresponding EDS image (b) of the carbon-coated ion-doped vanadium oxide prepared in Example 1.

[0028] Figure 3 The carbon-coated ion-doped vanadium oxide (a) prepared in Example 1 and the VO prepared in Comparative Example 1 are shown. 2 and FeVO prepared in Comparative Example 2 2 (b) XRD pattern.

[0029] Figure 4 The sodium ion battery prepared in Example 1 is shown as 1 mV s -1 Cyclic voltammetry curves of the first three cycles at the scan rate.

[0030] Figure 5 The sodium ion battery prepared in Example 1 is shown in FIG. -1 , 0.4 mV s -1 , 0.6 mV s -1 , 0.8mV s -1 , 1 mV s -1 Capacitance contribution percentage at five scan speeds.

[0031] Figure 6 The sodium ion batteries prepared by using the products obtained in Example 1, Comparative Example 1 and Comparative Example 2 as positive electrode active materials have a high conductivity at 0.1 A g -1 Long cycle performance diagram at current density of .

[0032] Figure 7 The sodium ion battery 0.5 A g prepared in Example 1 -1 Long cycle performance diagram at current density of . DETAILED DESCRIPTION

[0033] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0034] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.

[0035] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.

[0036] Example 1 The present invention provides a method for preparing a carbon-coated ion-doped vanadium oxide material, comprising the following steps: (1) Preparation of vanadium oxide intermediate solution: In a beaker, add 1.2 g V 2 O 5 With 2.49 g H 2 C 2 O 4 ·2H 2 O was added to 40 ml of deionized water and stirred in a water bath at 80 °C for 1 h to obtain a dark blue vanadium oxide intermediate VOC 2 O 4 Solution; (2) Take 30 ml of vanadium oxide intermediate VOC 2 O 4 The solution was added to a 100 ml reactor, and then 3 ml of H 2 O 2 , 20 ml methanol, stirred at room temperature for 30 min; 0.9 g glucose and 0.16 g Fe(NO 3 ) 3 9H 2O, mixed and stirred for 10 min, and then placed in a forced air oven for solvothermal reaction at 170 °C for 48 h; (3) The obtained solid was repeatedly washed with deionized water and ethanol. The obtained product was vacuum dried at 60°C for 12 h, and then the dried powder was calcined at a heating rate of 2°C / min to 550°C. The constant temperature was maintained for calcination for 2 h to obtain carbon-coated ion-doped vanadium oxide.

[0037] This embodiment also provides a method for preparing a positive electrode sheet, comprising the following steps: The carbon-coated ion-doped vanadium oxide prepared above was weighed, and mixed with a conductive agent, conductive carbon black, and a binder, polyvinylidene fluoride, in a mass ratio of 8:1:1, and then fully ground. Then, N-methyl-2-pyrrolidone was added dropwise with a pipette and stirred until uniform. Then, the mixed electrode material was coated on an aluminum foil, vacuum dried for 12 h, and cut into circular electrode sheets to obtain positive electrode sheets.

[0038] This embodiment also provides a method for preparing a sodium ion battery, comprising the following steps: In the glove phase, a sodium metal sheet was used as the negative electrode, the positive electrode sheet prepared as described above was used, a glass fiber membrane (GF / D) was used as a separator, NaPF6 was selected as the electrolyte, and the solvent was DEC:EC=1:1 Vol% with 5% FEC, and a 2032 button battery was assembled by a battery packaging machine.

[0039] Example 2 The difference between Example 2 and Example 1 is that the types of doped metal ions are different. The 0.16 g Fe(NO 3 ) 3 9H 2 O was replaced by adding 0.116 g Ni(NO 3 ) 2 6H 2 O, the rest of the process is exactly the same.

[0040] The sodium ion battery prepared in this example has a current density of 0.1 A g -1 The initial capacity is 110 mA h g -1 , the capacity retention rate after 200 cycles is 98%.

[0041] Example 3 The difference between Example 3 and Example 1 is that the solvent thermal reaction time in step (2) is different, specifically 24 h, and the rest of the process is exactly the same.

[0042] The sodium ion battery prepared in this example has a current density of 0.1 A g -1The initial capacity is 105 mA h g at a current density of -1 , the capacity retention rate after 200 cycles is 95%.

[0043] Example 4 The difference between Example 4 and Example 1 is that in step (1), the preparation temperature of the vanadium oxide intermediate solution is different, specifically room temperature, and the rest of the processes are exactly the same.

[0044] The details are as follows: In a beaker, 1.2 g V 2 O 5 With 2.49 g H 2 C 2 O 4 ·2H 2 O was added to 40 ml of deionized water and stirred at room temperature for 24 h to obtain a dark blue vanadium oxide intermediate VOC 2 O 4 Solution.

[0045] The sodium ion battery prepared in this example has a current density of 0.1 A g -1 The initial capacity is 90 mA h g -1 , the capacity retention rate after 200 cycles is 100%.

[0046] Comparative Example 1 This comparative example provides a VO 2 The preparation method comprises the following steps: (1) Preparation of vanadium oxide intermediate solution: In a beaker, add 1.2 g V 2 O 5 With 2.49 g H 2 C 2 O 4 ·2H 2 O was added to 40 ml of deionized water and stirred in a water bath at 80 °C for 1 h to obtain a dark blue vanadium oxide intermediate VOC 2 O 4 Solution; (2) Take 30 ml of dark blue vanadium oxide intermediate VOC 2 O 4 The solution was added to a 100 ml reactor, and then 3 ml of H 2 O 2 , 20 ml methanol, stirred at room temperature for 30 min, and then placed in a forced air oven for hydrothermal reaction at 170°C for 48 h. The solid obtained after the hydrothermal reaction was washed by centrifugation with deionized water and ethanol several times, and the obtained product was vacuum dried at 60°C for 12 h to obtain VO 2 .

[0047] Comparative Example 2 This comparative example provides a Fe 3+ Doped VO 2 The preparation method comprises the following steps: (1) Preparation of vanadium oxide intermediate solution: In a beaker, add 1.2 g V 2 O 5 With 2.49 g H 2 C 2 O 4 ·2H 2 O was added to 40 ml of deionized water and stirred in a water bath at 80 °C for 1 h to obtain a dark blue vanadium oxide intermediate VOC 2 O 4 Solution; (2) Take 30 ml of dark blue vanadium oxide intermediate VOC 2 O 4 The solution was added to a 100 ml reactor, and then 3 ml of H 2 O 2 , 20 ml methanol, stirred at room temperature for 30 min; 0.9 g glucose and 0.16 g Fe(NO 3 ) 3 9H 2 O, mixed and stirred for 10 min, and then placed in a forced air oven for hydrothermal reaction at 170°C for 48 h; the solid obtained after the hydrothermal reaction was centrifuged and washed several times with deionized water and ethanol, and the obtained product was vacuum dried at 60°C for 12 h to obtain Fe 3+ Doped VO 2 FeVO 2 .

[0048] The samples obtained in Example 1 and the comparative example were characterized and analyzed, and the results are as follows: Figure 1 (a) is a SEM image of the carbon-coated ion-doped vanadium oxide prepared in Example 1, compared with Figure 1 (b) Comparative Example 1 Figure 1 (c) The SEM image of Comparative Example 2 shows that the VO synthesized before carbon coating 2 and FeVO 2 The microscopic morphology is a flower-like structure composed of aggregated nanosheets, while the microstructure after carbon coating is a flower-like structure coated on the surface, proving successful coating.

[0049] Figure 2 TEM and EDS images of the material obtained in Example 1. Figure 2As shown in (a), the central part is agglomerated vanadium oxide material, and the edge part is amorphous carbon material without lattice fringes. The edge material appears as a halo under selected electron diffraction, proving that it is amorphous. Figure 1 and Figure 2 (b) In EDS, the C element is evenly distributed in the selected area, while V, O, and Fe are only distributed in the central part, proving successful carbon coating.

[0050] Figure 3 (a) is the XRD pattern of the material prepared in Example 1, compared with Figure 3 (b) The XRD patterns of Comparative Examples 1 and 2 show that VO 2 and FeVO 2 The diffraction peaks at 15.6°, 25.3°, and 30.2° correspond to VO 2 (PDF#97-019-6175) The characteristic peaks of (001), (110), and (002) crystal planes, while the diffraction peaks at 24.2°, 33.0°, 36.4°, 41.3°, and 54.0° after carbon coating correspond to V 2 O 3 (PDF#97-009-4768) The characteristic peaks of the (012), (104), (110), (113), and (116) crystal planes at 27.9° correspond to the diffraction peaks of VO 2 (PDF#97-064-7604) Characteristic peaks of (011) crystal plane. It proves that there is a phase transformation process after carbon coating.

[0051] Electrochemical tests and analyses were performed on the samples obtained in Example 1 and the comparative example, and the results are as follows: Figure 4 For Example 1 at 1 mV s -1 The cyclic voltammetry curves obtained at a scan rate of 2.5 V show two broad peaks at 0.4 V and 0.75 V during the initial discharge process, corresponding to the embedding of sodium ions and the formation of SEI film, respectively. The broad peaks around 0.5 V to 2.2 V can be explained as the Na + The subsequent CV curves almost overlap, indicating good reversibility, and the broad redox peaks in the CV curves show obvious pseudocapacitive behavior. Therefore, the pseudocapacitive effect of Na on CV was tested by CV at different scan rates. + Storage contributions, such as Figure 5 As shown, at 0.2 mV s -1 , 0.4mV s -1 , 0.6 mV s -1 , 0.8 mV s -1 , 1 mV s -1When the scan rate increases, the pseudocapacitive contribution is 50.2%, 56.1%, 59.7%, 65.3% and 69.4%, respectively, indicating that as the scan rate increases, the pseudocapacitive portion also increases. Therefore, the sodium ion battery obtained in Example 1 has excellent capacity retention and cycle life.

[0052] Figure 6 The sodium ion batteries prepared by using the products obtained in Example 1, Comparative Example 1 and Comparative Example 2 as positive electrode active materials have a high conductivity at 0.1 A g -1 Long cycle performance diagram under current density, where the charge and discharge voltage range is 0-3 V, and the initial capacity of VO2 corresponding to comparative example 1 is 230 mA h g -1 After 350 cycles, the capacity retention rate is 26%. 2 The initial capacity is 250 mA hg -1 After 350 cycles, the capacity retention rate was 48%, and the initial capacity of Example 1 was 130 mA h g -1 , the capacity retention rate is 100% after 350 cycles.

[0053] Figure 7 Shown as Example 1 at 0.5 A g -1 Long cycle performance at a current density of 1.17 W, with an initial capacity of 115 mAh g -1 , the capacity retention rate is 100% after 800 cycles.

[0054] In summary, the present invention improves the conductivity of vanadium oxide materials and the electrochemical stability during the cycle by embedding metal ions in vanadium oxide; by carbon coating the metal ion-doped vanadium oxide materials, the collapse problem caused by the change in crystal spacing during the cycle is alleviated, and the cycle stability of the vanadium oxide materials is greatly improved; the raw material source of the present invention is convenient, the stability is good, the preparation method is simple to operate, and the cost is low. Therefore, the present invention effectively overcomes various shortcomings in the prior art and has a high industrial utilization value.

[0055] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a carbon-coated ion-doped vanadium oxide material, characterized in that: The reaction solution containing doped metal ions, vanadium oxide intermediate solution, oxidant, solvent and glucose is subjected to solvothermal reaction, and the obtained solid is calcined under a protective atmosphere to obtain a carbon-coated ion-doped vanadium oxide material; the doped metal ions are selected from Fe 3+ 、Ni 2+ and Cu 2+ One or more of .

2. The preparation method according to claim 1, characterized in that: The chemical formula of the vanadium oxide intermediate in the vanadium oxide intermediate solution is VOC2O4.

3. The preparation method according to claim 2, characterized in that: The preparation method of the vanadium oxide intermediate solution is: V2O5 and oxalic acid are dispersed in water, and the vanadium oxide intermediate solution is prepared after reaction at 60-80°C; the feeding mass ratio of the V2O5 to the oxalic acid is (0.5-2): (1-5).

4. The preparation method according to claim 1, characterized in that: The oxidant is selected from one or more of hydrogen peroxide, ammonium persulfate and potassium dichromate; the solvent is one or a combination of methanol and ethanol.

5. The preparation method according to claim 1, characterized in that: The volume ratio of the vanadium oxide intermediate solution, the oxidant and the solvent is (10-50): (3-5): (10-30).

6. The preparation method according to claim 1, characterized in that: The doped metal ions are added in the form of soluble metal salts, and the mass ratio of the soluble metal salt to glucose is (0.05-0.2): (0.5-1).

7. The preparation method according to claim 1, characterized in that: The solvent thermal reaction temperature is 160~200℃, and the reaction time is 24~48 h.

8. The preparation method according to claim 1, characterized in that: The calcination temperature is 300~600℃ and the time is 1~3h.

9. A carbon-coated ion-doped vanadium oxide material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the carbon-coated ion-doped vanadium oxide material as claimed in claim 9 as a positive electrode active material in the preparation of a sodium ion battery.

Citation Information

Patent Citations

  • Preparation method of lithium ion battery negative electrode spherical V2O3 / C composite material with multilevel structure

    CN103553131A

  • Method for adjusting band gap of vanadium dioxide powder

    CN104276602A

  • Vanadium oxide ultra-thin nanobelt with embedded ions and preparation method and application thereof

    CN105006561A

  • Copper ion or bismuth ion doped vanadium oxide material as well as preparation method and application thereof

    CN113401941A

  • Preparation method of coal pitch-based V2O3-C composite material

    CN114678503A